Data on cytotoxicity in HeLa and SU-DHL-4 cells exposed to DPB162-AE compound - Mart Bittremieux; Katsuhiko Mikoshiba; Geert Bultynck (Data in Brief, 2017)
DPB162-AE is a valuable tool to study store-operated Ca2+ entry (SOCE), as this compound was developed as a 2-APB analog that inhibits SOCE more potently and more selectively than 2-APB itself. In addition to this, we showed that, in some conditions, DPB162-AE can deplete the endoplasmic reticulum Ca2+ stores in intact cells, including the cervical carcinoma HeLa cell line and the diffuse large B-cell lymphoma SU-DHL-4 cell line. Here, we present data regarding the toxicity of DPB162-AE in HeLa and SU-DHL-4 cells. For further interpretation of the data presented in this article, please see the research article ‘DPB162-AE, an inhibitor of store-operated Ca2+ entry, can deplete the endoplasmic reticulum Ca2+ store’ (M. Bittremieux, J. V. Gerasimenko, M. Schuermans, T. Luyten, E. Stapleton, K.J. Alzayady, et al., 2017) [1].